Effects of Locust Bean Gum Intake on Defecation and Intestinal Environment in Healthy Volunteers - KAWAI, Shuji; HONDA, Yasuki; ARA, Katsutoshi; YOSHIMATSU, Tadashi (Journal of Intestinal Microbiology, 2002)
The effects of locust bean gum intake at 5 g/day level for 2 weeks on defecation, fecal conditions and their metabolites were studied in 20 healthy volunteers. The fecal pH value was significantly dropped, and the fecal contents of putrefactive products, such as the concentrations of each ammonia and total amine, were also tended to decrease. Improvement of fecal consistency, change of fecal color from dark brown to yellowish brown, decrease of fecal odor and increase in defecation frequency of persons whose frequency was relatively low were observed after administration. The fecal contents of short-chain fatty acids (SCFA), especially acetic acid, butyric acid and propionic acid, were increased. These results suggested that the locust bean gum intake at 5 g/day level could improve the intestinal environment.